Pengaruh Environmental, Social and Governance (ESG) Disclosure, Managerial Ownership, dan Gender Diversity pada Nilai Perusahaan Sektor Industri di Bursa Efek Indonesia Tahun 2021 – 2024 - Risma Putri Sugiarti; Yuyun Isbanah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Firm value is essentially the price or worth of a business in the eyes of the market, which indicates how the public assesses its performance and condition. The focus of this study is to determine how the firm value of industrial companies listed on the Indonesia Stock Exchange during the 2021–2024 period is influenced by environmental, social, and governance (ESG) disclosure, managerial ownership, and gender diversity. The data used is quantitative data sourced from secondary sources. Industrial companies listed on the Indonesia Stock Exchange during the 2021–2024 period constitute the population in this study. The sample was selected using purposive sampling, with a total of 46 companies. Data were calculated using STATA 17, and panel regression was used for analysis. The results showed that governance disclosure had a negative and significant effect on firm value. Conversely, environmental disclosure, social disclosure, managerial ownership, and gender diversity did not significantly influence firm value.